2007
DOI: 10.1159/000098483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Chromium on Resistance Artery Function and Nitric Oxide Signaling in the Sucrose-Fed Spontaneously Hypertensive Rat

Abstract: Background: Consumption of high-glycemic index foods contributes to the development of hypertension in some patients. Likewise, in spontaneously hypertensive rats (SHR), high sucrose promotes a secondary rise in systolic blood pressure (SBP). Chromium (III) (Cr3+) prevents sucrose-induced hypertension, but leaves the basal hypertension that characterizes SHR intact. Methods: Since hypertension entails increased peripheral resistance, we compared effects of Cr3+ on resistance arteries from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 109 publications
5
15
0
2
Order By: Relevance
“…This suggests that the NO system was more active in the NBC group. Accordingly, this supports the contention that a relatively depressed NO system is involved in sugar-induced hypertension [5] and that NBC can affect this system as well as the RAS.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This suggests that the NO system was more active in the NBC group. Accordingly, this supports the contention that a relatively depressed NO system is involved in sugar-induced hypertension [5] and that NBC can affect this system as well as the RAS.…”
Section: Discussionsupporting
confidence: 82%
“…Kopilas et al [5] examined sugar-induced hypertension and concluded that the NO system was significantly involved in the pathogenesis. We examined the ability of LNAME, a substance that can inhibit the dilatory actions of NO, to influence SBP and found a trend to raise the blood pressure, more so in the NBC group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Cr(pic)3 has been extensively investigated in relation to carbohydrate metabolism, there are only a few studies devoted to its effects on the cardiovascular system [14, 17, 19, 2427, 29]. The consideration of the cardiovascular effects of the supplement becomes more relevant in view of the documented association between type 2 diabetes/glucose intolerance and cardiovascular disorders such as abnormal vascular function, increased blood pressure and augmented susceptibility to ischemic heart disease [3, 4, 11, 28].…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory and clinical studies indicate that certain forms of trivalent chromium have the capability to: (a) increase fat loss while preserving muscle [9,10]; (b) overcome insulin resistance and ameliorate diabetes [5,8]; (c) suppress free radical formation [11]; (d) lower total cholesterol and low-density lipoprotein (LDL) [12]; (e) decrease systolic blood pressure (SBP) [11,13]; (f) influence fluid and electrolyte balance [13]; (g) alter catecholamine metabolism [14] and (h) influence nitric oxide (NO) functions [15]. Finally, a recent report also suggests that trivalent chromium may increase useful lifespan, at least in rodents [16].…”
Section: Introductionmentioning
confidence: 99%